Properties of Concrete Containing Unground Palm Oil Fuel Ash as Partial Sand Replacement - Wan Ahmad, Saffuan; Khairunisa, Muthusamy; Hashim, Mohd Hanafi; Yaacob, Maizatil Akma (Trans Tech Publications, 2017)
The growing construction industry that demands for more natural sand supply has indirectly causes the escalation of river sand mining activity. Excessive sand mining affects the water quality and habitats of aquatic life. At the same time, the continuous dumping of palm oil fuel ash, a by-product of oil palm mill causes pollution to the environment. In order to preserve the natural sand and reduce amount of palm oil fuel ash disposed as waste, the present study investigates the potential use of palm oil fuel ash in concrete production. Thus, the effect of unground palm oil fuel ash as partial sand replacement towards workability and compressive strength of concrete is discussed in this paper. A total of six mixes were used in this experimental work. Plain concrete containing 100% river sand was used as reference specimen. The rest of the mixes were prepared by integrating unground palm oil fuel ash by 2%, 4%, 6%, 8% and 10% by weight of sand. All specimens were prepared in form of cubes and subjected to water curing until the testing age. Slump test were conducted on the fresh mix to determine the concrete workability. Compressive strength test were conducted at 7, 14 and 28 days. The finding shows that addition of unground palm oil fuel ash up to 8% does not have significant effect on concrete workability. In terms of compressive strength, inclusion of 6% unground palm oil fuel ash increases the strength of concrete by approximately 13%.